Molecular cloning, phylogenetic analysis and developmental expression of a vitellogenin (Vg) gene from the intertidal copepod Tigriopus japonicus - Lee, Kyun-Woo; Hwang, Dae-Sik; Rhee, Jae-Sung; Ki, Jang-Seu; Park, Heum Gi; Ryu, Jae-Chun; Raisuddin, Sheikh; Lee, Jae-Seong (ELSEVIER SCIENCE INC, 2008)
Vitellogenin (Vg) is the precursor of egg yolk protein vitellins, which serve as energy resource for embryonic development. Vg measurement has been used as a biomarker of exposure to endocrine-disrupting chemicals (EDCs). Therefore, Vg gene structure has been identified from several species used in environmental monitoring of EDCs. Among the copepods, except from the salmon louse, there is no report on Vg genes or their products. By using molecular cloning, we determined the full Vg gene sequence from the intertidal copepod, Tigriopus japonicus. The full cDNA sequence was of 5692 bp containing 5529 bp of open reading frame (ORF) encoding for 1842 amino acids. The phylogenetic analysis revealed that T.japonicus; Vg is distinct from the other arthropods as it formed a clade with salmon louse only. The expression of Vg transcripts was negligible in nauplii; detectable only at the copepodid stage 3. Females expressed over 270 times more Vg transcripts than males. The promoter sequence of T.japonicus Vg gene revealed an estrogen receptor (ER) half site and a metal response element (MIZE). When copepods were exposed to trace metals, cadmium after 96 h exposure caused significantly higher induction of Vg transcripts. Taken together, molecular analysis of T japonicus Vg would be helpful in understanding its role in development. Previous studies have established T japonicus as a potential model for testing of endocrine-disrupting chemicals (EDCs). The study of T japonicus Vg will fuel momentum in using this species in comparative molecular endocrinology and biomonitoring of EDCs. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: CAENORHABDITIS-ELEGANS; ENDOCRINE DISRUPTION; ESTROGENIC COMPOUNDS; OVARIAN DEVELOPMENT; BIOMARKER; EXPOSURE; XENOBIOTICS; CADMIUM; PROTEIN; REPRODUCTION